The effects of mental model conformity on usability in apps. (September 2013) - Fok, Audrey W.; Procci, Katelyn; Flynn, Jeremy R.; Mouloua, Mustapha
Designing interfaces to conform to users' mental models is an important usability guideline. With respect to designing apps to be used on tablets and smartphones for existing websites, whether the app conforms exactly to the website's original layout is a design question that must be considered. Aside from general mental models of functionality, this study sought to examine the importance of conformity to system (i.e., website) mental models when designing apps. Sixteen undergraduate students were recruited. They completed a series of tasks, either first on the website to generate a mental model of the system, and then again on the app, or vice-versa. Time to complete the tasks was recorded and participants also completed questionnaires to determine how system mental models affected usability. Results suggested that the app was more usable than the website overall. Task times and usability scores were not affected by condition; however, those who used the website first gave higher subjective usability scores overall to both the app and the website. These results imply that conformity to the website is not necessary to create a usable app.